Synthesis and evaluation of novel non-enzymatic solid phase nanocomposites for hydrogen peroxide sensors / Farnaz Lorestani - Farnaz, Lorestani (2015)
Glassy carbon electrode (GCE) was modified with six novel solid-phase nanocomposites as substrate for non-enzymatic hydrogen peroxide (H2O2) sensor have been utilized in this study. This work was conducted to study the effect of different novel solid-phase nanocomposites with different morphologies toward H2O2, and also evaluate and enhance the performance of modified glassy electrodes with the prepared nanocomposites as hydrogen peroxide sensor. The first four composites were based on polyaniline as the polymer matrix. Silver nanoparticles-polyaniline nanotubes (AgNPs-PANINTs(A)) composite prepared via one-step modified free chemical template method and AgNO3 was used as the source of Ag nanoparticles (AgNPs). By reducing the temperature of the reaction, the nanotube morphology changed to rod shape and silver nanoparticle-polyaniline nanorods (AgNPs-PANINRs) composite is obtained. The AgNPs-PANINRs composite exhibited better electrochemical performance toward H2O2 detection with limit of detection (LOD) of 0.13 μMas compared to AgNPs-PANINTs(A) composite, due to higher surface area and content of AgNPs. The source of silver changed to Ag(NH3)2OH instead of AgNO3 in nanotube morphology of nanocomposite to get better distribution of AgNPs. The performance of the obtained composite (AgNPs-PANINTs(B)) with LOD of 0.6 μM significantly improved as compared to the nanotube composite prepared with AgNO3 as a source of silver. The combination of two different methods in synthesizing of the forth nanocomposite was conducted to obtain a better performance of materials for sensing H2O2. Silver nanoparticle-reduced graphene oxide-polyaniline nanofibers (AgNPs-PANINFs-rGO) were synthesized using two-step method. PANINFs were prepared in the presence of sulfuric acid applying vertical sonochemical method. AgNPs-rGO, which was prepared separately by hydrothermal method, was dropped on the surface of GCE followed by PANINFs to fabricate the modified electrode. The modified electrode was prepared by dropping the obtained AgNPs-rGO and PANINFs on the glassy carbon electrode (GCE). The prepared modified electrode shows LOD of 0.117 μM. This composite indicated smaller LOD as compared to AgNPs-PANINTs(B) and AgNPs-PANINRs composites due to the presence of rGO. The two last composites are carbon-based composites. Silver nanoparticles-reduced graphene oxide-carbon nanotubes (AgNPs-MWCNT-rGO) were prepared using two different methods which are hydrothermal (AgNPs-MWCNT-rGO(H))and electrochemical (AgNPs-MWCNT-rGO(E)). These methods provided the notable advantage of a single-step reaction without employing any toxic solvent or reducing agent by providing a novel green synthetic route to produce the AgNPS-MWCNT-rGO. The hydrothermal AgNPs-MWCNT-rGO(H) composite exhibited a LOD around 0.9 μM. Finally, the electrodeposited AgNPs-MWCNT-rGO(E) composite displayed LOD of 1.4 μM that is less than hydrothermal composite. All the synthesized nanocomposites were characterized by using X-ray Diffraction, Field Emission Scanning Electron Microscopy, Transmission Electron Microscopy and Atomic Force Microscopy meanwhile the reactivity of the prepared composites towards H2O2 were analyzed using cyclic voltammetry and chronoamperometry. All the nanocomposites modified electrodes exhibited excellent electrocatalytic activity for the reduction of H2O2 with a fast amperometric response time less than 3 s. Among all six prepared nanocomposites, AgNPs-PANINFs-rGO composite is the best solid-phase nanocomposites system for H2O2 detectionwith LOD = 0.117 μM.